2010
DOI: 10.1007/s11010-010-0409-6
|View full text |Cite
|
Sign up to set email alerts
|

High fat diet induces ceramide and sphingomyelin formation in rat’s liver nuclei

Abstract: Obesity increases the risk for hepatic steatosis. Recent studies have demonstrated that high fat diet (HFD) may affect sphingolipid formation in skeletal muscles, heart, and other tissues. In this work we sought to investigate whether HFD feeding provokes changes in content and fatty acids (FAs) composition of sphingomyelin and ceramide at the level of liver and hepatic nuclei. Furthermore, we investigated whether the ceramide formation is related to the activity of either neutral sphingomyelinase (N-SMase) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 48 publications
7
55
2
Order By: Relevance
“…This results, thereby, indicate that an enhancement in the content of CER was a consequence of increased formation of the compound from sphingomyelin. It seems that hyperthyroidism may increase activity of acidic SMase, which in turn elevates CER level, as has been reported for liver tissue homogenates, cultured hepatocytes [38] as well as in the adipose tissue of ob/ob mice [39] and high fat diet induced obesity in rodent models [40]. On the other hand, the present study also demonstrated that hyperthyroidism expressively increased sphingomyelin level.…”
Section: Discussionsupporting
confidence: 87%
“…This results, thereby, indicate that an enhancement in the content of CER was a consequence of increased formation of the compound from sphingomyelin. It seems that hyperthyroidism may increase activity of acidic SMase, which in turn elevates CER level, as has been reported for liver tissue homogenates, cultured hepatocytes [38] as well as in the adipose tissue of ob/ob mice [39] and high fat diet induced obesity in rodent models [40]. On the other hand, the present study also demonstrated that hyperthyroidism expressively increased sphingomyelin level.…”
Section: Discussionsupporting
confidence: 87%
“…CER is synthesized from serine and palmitoyl-CoA or hydrolysis of SM by acid sphingomyelinase (ASM). HFD is known to increase CER and SM in liver [64]. The present observation of decreased SM and CER levels in HFD-fed CYP7A1-tg mice indicated that bile acids might reduce HFD-induced increase of SM and CER.…”
Section: Discussionmentioning
confidence: 47%
“…1). Interestingly, the abundance and/or activity of either neutral or acid sphingomyelinases has been reported to be elevated in the adipose tissue of ob/ob and high-fat diet-induced obese mice as well as in liver in response to high-fat feeding [38,78,79]. Furthermore, a recent study demonstrated that exposure of C2C12 myotubes to exogenous sphingomyelinase can elevate intracellular ceramide levels; however, effects on insulin sensitivity were not determined in this particular study [80].…”
Section: Influence Of Caveolae In Mediating the Effects Of Ceramidementioning
confidence: 86%